Pengaruh Penambahan Ekstrak Meniran (Phyllantus niruri L.) terhadap Karakteristik Kimia dan Sensoris Hard Candy - Enrica Balanzi, Dhenabe; Suparthana, Putu; Diah Puspawati, Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2024)
The meniran plant is a medicinal plant that has many ingredients that are good for the body. One use of the meniran plant is to process it into hard candy. This study aims to determine the effect of adding meniran extract on the characteristics of hard candy, and determining the correct addition of meniran extract so that it can produce hard candy with the best characteristics. The experimental design used was a Completely Randomized Design (CRD) with additional extract treatment consisting of 5 levels: 0%; 0.30%; 0.60%; 0.90%; 1.20%. The treatment was repeated 3 times to obtain 15 experimental units. Data were analyzed using variance and treatments that had a significant effect were followed by Duncan's Multiple Range Test (DMRT). The addition of meniran extract to hard candy has a significant effect on water content, ash content, antioxidant activity, and hedonic tests (color, aroma, texture, taste, and overall acceptability). Hard candy that has the best characteristics is obtained by adding 0,90% meniran extract with a water content value of 1,83%; ash content 0,14%; antioxidant activity 63,50%; texture, aroma, taste, color, and overall acceptability are favorable.